Secondary Involvement of the Penis by Non-Hodgkin Lymphoma - PEKER, ABDUSSELİM ADİL; Timocin Yigman, Gizem; SHARIFOV, RASUL; PEKER, ABDUSSELİM ADİL; TOPRAK, HÜSEYİN; SHARIFOV, RASUL; TOPRAK, HÜSEYİN (My University, 2021)
Primary penile lymphoma is extremely rare and there are less than 30 reported cases worldwide. Frequently penile lymphoma is seen as a secondary involvement of the penis by lymphoma, most likely by Non-Hodgkin lymphoma (NHL). Here, we report a case with penile lymphoma caused by previously known NHL.
Keywords: Non-Hodgkin lymphoma; penis; MRI; penile lymphoma